Perlindungan Hukum terhadap Anak yang Sedang Menjalani Proses Pembinaan di Lembaga Pembinaan Khusus Anak - Supriyatna; Adi Sujatno; Umar Aris (Syntax Literate, 2023)
Children who grow up in an environment that contains educated, polite, friendly people tend to follow people around them because what is seen is the manners carried out by adults. If the child grows up in an environment that contains uneducated people or even surrounded by perpetrators of crime, then the child will be more likely to behave violently and not hesitate to commit crimes or violence. The research method that the author uses is the normative juridical method, which is research that prioritizes literature data, namely research on secondary data. The secondary data can be primary, secondary or tertiary legal material. This research includes research on positive legal provisions in force in Indonesia relating to legal protection of children who are undergoing the formation process at the Special Child Development Institute (LPKA). Based on the results of the study, the author concludes that the form of legal protection for children who undergo the formation process at the Special Child Development Institute is the right to worship in accordance with their respective religions and beliefs, the right to get care both physical and spiritual care, the right to education and teaching, the right to get proper health and food services, the right to complain, the right to get reading materials and to follow broadcasts Other mass media that are not prohibited, entitled to visits by family, legal counsel, or certain other persons, are entitled to reduced criminal terms (remission), parole (assimilation), leave (leave to visit family and leave before release.